THE INFLUENCE OF SCHOOL INFRASTRUCTURE ARRANGEMENT, SAFETY, AND COMFORT ON STUDENTS’ MOTIVATION TO PARTICIPATE IN LEARNING: A STUDY OF JUNIOR HIGH SCHOOL INFRASTRUCTURE IN KABUPATEN CIANJUR - Mandalora, Charle Richard; Ahmad, Masduki; Sutomo, Sugiarto (Proceeding of International Seminar on Humanity, Education, and Language, 2025)
A Study of junior high school access to education has an important indicator, namely the educational participation rate, which is used to measure the level of public engagement in the educational system each year. A prevailing issue is the persistently low average duration of study participation across various regions in Indonesia. This study focuses on junior high schools in Kabupaten Cianjur. The research aims to identify key variables that can contribute to enhancing students’ motivation to participate in learning activities. The primary focus will be on the provision, arrangement, safety, and comfort of school infrastructure. Data will be collected through questionnaires distributed to teachers in several schools, as well as direct interviews with a number of junior high school principals in Kabupaten Cianjur. The findings will highlight important contributing factors to increased motivation. The results of this study may serve as valuable input and a foundation for future education policy decisions.